2022
DOI: 10.23887/jppsh.v5i3.39797
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Layanan Kesehatan Maternal, Neonatal, dan Keluarga Berencana (KB) pada Masa Pandemi Covid-19 di Praktik Mandiri Bidan

Abstract: Masa Pandemi COVID-19 menghabat seluruh komponen kehidupan, tidak terkecuali pelayanan kesehatan termasuk pelayanan kesehatan ibu dan anak di Praktik Mandiri Bidan (PMB). Tujuan penelitian ini menganalisis pelaksanaan layanan Maternal, Neonatal, dan Keluarga Berencana pada masa pandemic covid-19. Penelitian ini merupakan deskriptif kuantitatif survey. Populasi dalam penelitian ini adalah semua Praktik Mandiri Bidan yang ada berjumlah 52 PMB. Sampel yang digunakan PMB sebanyak 47 orang, data diambil menggunakan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
0
0
3
Order By: Relevance
“…Independent practice midwives play a good role in providing maternity services in the practice place by continuing to carry out maternity assistance according SOPs and still comply with the established health protocols. This study is in line with research conducted by independent practice midwives in Buleleng district, who showed that midwives performed maternity services well, referring to service standards during the Covid-19 pandemic, according to standards guidelines from Ministry of Health (13). This is also in accordance with the guidelines for pregnant, Postpartum, Maternity, and New Babies in the pandemic period by Ministry of Health of Republic Indonesia in 2020 which states that in carry out maternity services, the principles of Covid-19 prevention must be carried out, wearing level 2 PPE, and the place of maternity assistance is also determined based on the status of the mother who confirmed to have Covid-19 or not complication disease (14).…”
Section: Discussionsupporting
confidence: 89%
“…Independent practice midwives play a good role in providing maternity services in the practice place by continuing to carry out maternity assistance according SOPs and still comply with the established health protocols. This study is in line with research conducted by independent practice midwives in Buleleng district, who showed that midwives performed maternity services well, referring to service standards during the Covid-19 pandemic, according to standards guidelines from Ministry of Health (13). This is also in accordance with the guidelines for pregnant, Postpartum, Maternity, and New Babies in the pandemic period by Ministry of Health of Republic Indonesia in 2020 which states that in carry out maternity services, the principles of Covid-19 prevention must be carried out, wearing level 2 PPE, and the place of maternity assistance is also determined based on the status of the mother who confirmed to have Covid-19 or not complication disease (14).…”
Section: Discussionsupporting
confidence: 89%
“…Setiap jenis kontrasepsi memiliki efektivitas dalam mencegah kehamilan, tetapi juga memiliki efek samping yang berbeda yang dapat mengganggu kesehatan dan keindahan tubuh, seperti kegemukan atau wajah berjerawat. Akibatnya banyak pengguna kontrasepsi hormonal mengganti alat kontrasepsi yang sudah digunakan ke jenis kontrasepsi yang lain (Aqmal, 2020;Sugandini et al, 2021). Saat ini pergantian metode kontrasepsi oleh akseptor dalam 5 tahun terakhir meningkat, yang berganti metode kontrasepsi baru satu kali sebanyak 48 persen dan berganti metode kontrasepsi lebih dari satu kali sebesar 18 persen (Mandira et al, 2020).…”
Section: Diskusiunclassified
“…Dalam hal kepatuhan tenaga kesehatan menggunakan APD, selama pandemi COVID-19 tenaga kesehatan yang memberikan pelayanan kesehatan diharuskan menggunakan APD yang disesuaikan dengan tempat dan jenis pelayanan yang diberikan. Sugandini et al 11 memaparkan bahwa kepatuhan petugas kesehatan menggunakan APD saat melakukan pelayanan membuat rasa takut akan paparan COVID-19 pada ibu hamil berkurang dan memotivasi untuk tetap melakukan pemeriksaan antenatal di fasilitas kesehatan. Andriani et al 31 memaparkan bahwa kepatuhan tenaga kesehatan dalam menggunakan APD akan memberi perasaan aman bagi tenaga kesehatan dalam bekerja.…”
Section: Bahasanunclassified